2013
DOI: 10.1128/iai.01269-12
|View full text |Cite
|
Sign up to set email alerts
|

Complex T Cell Interactions Contribute to Helicobacter pylori Gastritis in Mice

Abstract: Disease due to the gastric pathogen Helicobacter pylori varies in severity from asymptomatic to peptic ulcer disease and cancer. Accumulating evidence suggests that one source of this variation is an abnormal host response. The goal of this study was to use a mouse model of H. pylori gastritis to investigate the roles of regulatory T cells (Treg) as well as proinflammatory T cells (Th1 and Th17) in gastritis, gastric T cell engraftment, and gastric cytokine production. Our results support published data indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 48 publications
2
62
0
4
Order By: Relevance
“…Many data support the idea that the Th17 response favors the bacterial growth in mice and contributes to the inflammation both in mice and in humans (3)(4)(5), although its role is probably not essential because IFN-g has the largest effect (2). Along with this evidence, other data suggest that this response may exert a regulatory effect rather than a proinflammatory one (6).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Many data support the idea that the Th17 response favors the bacterial growth in mice and contributes to the inflammation both in mice and in humans (3)(4)(5), although its role is probably not essential because IFN-g has the largest effect (2). Along with this evidence, other data suggest that this response may exert a regulatory effect rather than a proinflammatory one (6).…”
mentioning
confidence: 63%
“…It is known that the infection by the bacterium is accompanied by a Th1 immune response that, instead of being useful for clearing the bacterium, is probably responsible for the mucosa damage (1). The paradigm that the Th1 profile is the only one that sustains H. pylori-associated diseases has been recently revised, because it has been demonstrated that other proinflammatory cytokines, besides IFN-g, such as IL-17 and TNF-a, are also involved (2).…”
mentioning
confidence: 99%
“…Th1 and Th17 cells are also associated with the gastric mucosal immune response elicited by H. pylori infection (Gray et al, 2013). It is therefore interesting that infected mice had reduced numbers of these cells in the spleen and CNS after EAE induction.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] The phenotypes of T helper subsets are determined by the local cytokine milieu and their lineage-specific transcription factors. [11][12][13] H. pylori elicits Th1 response to produce interferon-γ and tumor necrosis factor-α causing chronic gastritis and ulcers. [9,13] Th17 cells are also frequently recruited by H. pylori to the gastric mucosa, and are characterized by expression of interleukin (IL)-17A/F, granulocytemacrophage colony-stimulating factor (GM-CSF), IL-21, IL-22 and IL-23, and the transcription factor of RORγt.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] H. pylori elicits Th1 response to produce interferon-γ and tumor necrosis factor-α causing chronic gastritis and ulcers. [9,13] Th17 cells are also frequently recruited by H. pylori to the gastric mucosa, and are characterized by expression of interleukin (IL)-17A/F, granulocytemacrophage colony-stimulating factor (GM-CSF), IL-21, IL-22 and IL-23, and the transcription factor of RORγt. [11,14] While activation of Th17 cells contributes to bacterial eradication, [15] Th17-mediated immuneresponse can be detrimental to gastric epithelium during gastritis.…”
Section: Introductionmentioning
confidence: 99%